Cloud of ink - Klatt, L. S. (Iowa poetry prize., 2011)
On the surface, L. S. Klatt's poems are airy and humorous-with their tales of chickens wandering the highways of Ohio and Winnebago trailers rolling up to heaven and whales bumping like watermelons in a bathtub-but just under the surface they turn disconcertingly serious as they celebrate the fluent word. ℗¡Under the heat of inquiry, under the pressure of metaphor, the poems in Cloud of Ink liquefy, bend, and serpentine as they seek sometimes a new and sometimes an ancient destination. They present the reader with existential questions as they side-wind into the barbaric; the.